THE PRESENT-DAY SITUATION OF THE TRANSPORT AND LOGISTICS SECTORS IN POLAND AND BELARUS AND THE CHALLENGES TO THEIR DEVELOPMENT T - Demianiuk, Regina; Bandarenka , Natallia (Management and Administration Journal, 2020)
The article presents the condition of the transport and logistics sector, and the problems and challenges to the development of TFL companies in Poland and Belarus. Special attention has been paid to the condition of the transport and logistics market in Poland and Belarus and the logistic efficiency of Poland and Belarus analysed on the basis of the LPI developed by the World Bank. The position of Polish logistics was highly rated, while Belarus was outside the first hundred countries rated in accordance with the LPI. The transport and logistics sector is an important and prosperous branch of the Polish economy. Despite quite an active transport and logistics policy in Belarus, the market for logistics services is underdeveloped. The transport and logistics sector in Poland and Belarus operates in an environment subject to dynamic changes, such as digitization, artificial intelligence, Big Data, automation and e-commerce development. Among other things, the development of the TFL on both sides of the border will depend on the understanding and the need to adapt to the ongoing megatrends.